EXTH-11. PATIENT DERIVED INDUCED NEURAL STEM CELLS FOR TREATMENT OF GLIOBLASTOMA. (9th November 2020) - Buckley, Andrew; Hagler, Shaye; Lettry, Vivien; Bago, Juli; Maingi, Spencer; Khagi, Simon; Ewend, Matthew; Miller, C Ryan; Hingtgen, Shawn
Abstract: Induced neural stem-cells (iNSCs) represent a new opportunity in the emerging field of cellular immunotherapy. Patient-derived iNSCs modified to produce anti-tumoral compounds could lead to less rejection and safer outcomes than an off-the-shelf therapy. In this study, we established fibroblast lines (PFs) from skin-biopsies of patients being treated for glioblastoma (GBM) and transdifferentiated those fibroblasts into iNSC lines that produce anti-tumor compounds. We designed a combination of genomic and functional testing to assess iNSC line efficacy. Functional testing revealed differences in rate of transdifferentiation, therapeutic agent production, and tumor-homing amongst cell lines all of which varied among patients. RNAseq profiles of individual cells lines revealed biomarker signatures that differed in tumor-homing-pathways. There was no observed neuronal differentiation in the iNSCs from the transcriptomic profiles, indicating stability after transdifferentiation amongst PFs. Anti-tumor activity of patient-derived iNSCs was measured in vivo by surgical-resection mouse models with invasive CD133+ GBM cells. Patient-derived iNSCs showed variable tumoricidal effectiveness; more highly effective iNSC cells lines reduced tumor burden and increased survival post-resection from 28 to 45 days, whereas less effective cells lines could increase post-resection survival with increased iNSC dosage. PF origination and transcriptomic profile accounted for the differences amongst the iNSC lines. Identification of differentially expressed genes could indicate the cellular pathways that are most important for guaranteeing high, anti-tumoral activity. Further, the cellular profile of the patient-derived fibroblast influences the resulting cellular profile of the iNSC; potentially, correlation of fibroblast gene expression profile could predict tumoricidal efficacy of derived iNSCs.